Optimizing the Use of Oral Presentation Techniques to Teach Conversation for Specific Purposes - Pratami, Mentari; Dewi, Erniyanti Nur Fatahhela (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2025)
The study reports the result of the implementation of the use of oral presentation technique to teach conversation for the English for Specific Purpose conversation class.   The aim of the research is to know whether the oral presentation technique could bring about better result of the students’ communicative competence for specific purpose. The research method applied was a qualitative case study research design.  The participants of the research were 40 students of semester 5 academic year 2024/2025 of Bina Sarana Informatika University.  The data collection was done using a semi-structured interview, documentation, and classroom observation. Next, the data was analyzed using line by line analysis. The research result shows that the use of oral presentation technique to teach conversation for Specific Purpose was quite good. Comparing to the test result of the previous semester, there is significant improvement in term of the speaking skill and final test result. Students enjoyed doing the oral presentation by taking part actively in the discussion as well as in the question-and-answer session. The researcher also found out that some teaching aspects need to be improved such as time management, language function and form, and pronunciation capability. Based on the result and discussion, it is concluded that there is a significant improvement in term of the speaking skill and final test result.